2022
DOI: 10.3389/fdgth.2022.954069
|View full text |Cite
|
Sign up to set email alerts
|

Virtual conversational agents versus online forms: Patient experience and preferences for health data collection

Abstract: ObjectiveVirtual conversational agents, or chatbots, have emerged as a novel approach to health data collection. However, research on patient perceptions of chatbots in comparison to traditional online forms is sparse. This study aimed to compare and assess the experience of completing a health assessment using a chatbot vs. an online form.MethodsA counterbalanced, within-subject experimental design was used with participants recruited via Amazon Mechanical Turk (mTurk). Participants completed a standardized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Modern data collection tools allow survey designers to develop chatbot-based interactions to collect health data mimicking human-to-human conversations. Studies have shown that individuals prefer chatbot-based conversational data collection experience in comparison to traditional web-based forms [ 33 , 34 ]. Visual and graphical enhancements in REDCap appearance of surveys, patient communication, and researcher interface could support modernization of REDCap-based surveys, thus providing study staff and patients with clear and effective experience of health data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern data collection tools allow survey designers to develop chatbot-based interactions to collect health data mimicking human-to-human conversations. Studies have shown that individuals prefer chatbot-based conversational data collection experience in comparison to traditional web-based forms [ 33 , 34 ]. Visual and graphical enhancements in REDCap appearance of surveys, patient communication, and researcher interface could support modernization of REDCap-based surveys, thus providing study staff and patients with clear and effective experience of health data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that over 69% participants preferred chatbot for data collection with higher usability and net promoter scores for chatbot. [33] Chatbot provided superior engagement and interactivity and was perceived as more intuitive compared to standard, web-based REDCap interface. Future studies should look into better understanding of study staff and patient needs to optimize survey development and data collection experience.…”
Section: Limitationsmentioning
confidence: 99%
“…This design maintained steady progress and may have provided a good user experience, but this automated design and small interface may have been more difficult for some participants to read or review responses across the form. Previous research found that participants praised chatbots for being “ quick and easy ” despite taking longer to complete ( 28 , 30 ). The humanlike, conversational, and pleasant design of the chatbot may take longer but may also make it easier or more enjoyable to complete the health forms.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed older adults reported high perceived usefulness, ease-of-use, and satisfaction for the chatbot. Another study found most participants preferred a chatbot (Dokbot) to an online form (REDCap) even though the chatbot took longer to complete ( 28 ). Participants in this study perceived the chatbot as easy to use and feeling as though they were talking to a human with over 69% positive comments, showing a positive attitude towards the chatbot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation